Analisis Penyebab Terjadinya Pelecehan Seksual terhadap Laki-Laki di Moda Transportasi KRL Jabodetabek - Haryadi, Rahma Nur Isnaini; Abdullah, Mirna Nur Alia; Nurbayani K, Siti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research was initiated due to the phenomenon of sexual harassment encountered on commuter trains in the Greater Jakarta area (Jabodetabek). The aim of this study is to identify the factors causing sexual harassment against men on these commuter trains. This study employs a qualitative approach with a case study method. The results of the study indicate several factors contributing to the sexual harassment of men on Jabodetabek commuter trains. Regarding security factors, the limited number of available train officers and the perceived ineffectiveness of CCTV for passengers were noted. Additionally, the comfort factor was deemed insufficient due to overcrowded conditions among passengers on the trains. Furthermore, there is a low level of awareness and sensitivity among passengers to the situations occurring within the train.